Dr Malondialdehyde as an independent predictor of body mass index in adolescent girls - Klisic, Aleksandra (Journal of Medical Biochemistry, 2022)
Objective: Given the fact that the studies that examined oxidative stress in relation to obesity that included late adolescents are scarce and show inconclusive results we aimed to investigate a wide spectrum of nitro-oxidative stress biomarkers [i.e., malondialdehyde (MDA), xanthine oxidase (XO), xanthine oxidoreductase (XOD), xanthine dehydrogenase (XDH), advanced oxidation protein products (AOPP) and nitric oxide products (NOx), as well as an antioxidative enzyme, i.e., catalase (CAT)] in relation with obesity in the cohort of adolescent girls ages between 16 and 19 years old. Patients and Methods: A total of 59 teenage girls were included in this cross-sectional study. Binary logistic regression analysis was performed to examine possible associations between biochemical and nitro-oxidative stress markers and body mass index (BMI). Results: There were not significant differences between oxidative stress markers between normal weight and overweight/obese girls (i.e., AOPP, XOD, XO, XDH) and CAT, except for MDA (p<0.001) and NOx (p=0.010) concentrations which were significantly higher in overweight/obese adolescent girls. Positive associations were evident between BMI and high sensitivity C-reactive protein (hsCRP) (OR=2.495), BMI and uric acid (OR=1.024) and BMI and MDA (OR=1.062). Multivariable binary regression analysis demonstrated significant independent associations of BMI and hsCRP (OR=2.150) and BMI and MDA (OR=1.105). Even 76.3% of the variation in BMI could be explained with this Model. Conclusion: Inflammation (as measured with hsCRP) and oxidative stress (as determined with MDA) independently correlated with BMI in teenage girls.